NCI First International Workshop on The Biology, Prevention, and Treatment of Relapse After Allogeneic Hematopoietic Stem Cell Transplantation: Report from the Committee on the Epidemiology and Natural History of Relapse following Allogeneic Cell Transplantation - Pavletic, Steven Z. (2010)
Allogeneic hematopoietic stem cell transplantation (alloHSCT) is increasingly being used for treatment of hematological malignancies, and the immunologic graft-versus-tumor effect (GVT) provides its therapeutic effectiveness. Disease relapse remains a cause of treatment failure in a significant proportion of patients undergoing alloHSCT without improvements over the last 2–3 decades. We summarize here current data and outline future research regarding the epidemiology, risk factors and outcomes of relapse after alloHSCT. While some factors (e.g. disease status at alloHSCT or graft-versus-host disease (GVHD) effects) are common, other disease-specific factors may be unique. The impact of reduced-intensity regimens on relapse and survival still need to be assessed using contemporary supportive care and comparable patient populations. The outcome of patients relapsing after an alloHSCT generally remains poor even though interventions including donor leukocyte infusions can benefit some patients. Trials examining targeted therapies along with improved safety of alloHSCT may result in improved outcomes, yet selection bias necessitates prospective assessment to gauge the real contribution of any new therapies. Ongoing chronic GVHD or other residual post-alloHSCT morbidities may limit the applicability of new therapies. Developing strategies to promptly identify patients as alloHSCT candidates, while malignancy is in more treatable stage, could decrease relapses rates after alloHSCT. Better understanding and monitoring of minimal residual disease post-transplant could lead to novel pre-emptive treatments of relapse. Analyses of larger cohorts through multi-center collaborations or registries remain essential to probe questions not amenable to single center or prospective studies. Studies need to provide data with detail on disease status, prior treatments, biological markers and post-transplant events. Stringent statistical methods to study relapse remain an important area of research. The opportunities for improvement in prevention and management of post alloHSCT relapse are apparent, but clinical discipline in their careful study remains important.